Microbial Effects from Biogas Slurry Application on Growing Phase of Turi (Sesbania grandiflora) - Nurzainah Ginting; Hasnudi .; Yunilas .; M Adanan Purba (Jurnal Peternakan Integratif, 2019)
This research was conducted in Samosir Island, North Sumatera Province, Indonesia  which has Inceptisol soil. As this type of soil is generally unfertile, since hundreds years ago, local people added ruminant faeces before planting. This research objective was to prove that application of biogas slurry on growing phase of Turi (Sesbania grandiflora) plant improved microbial population on soil thus plant quality.  This research was conducted from May until September 2018.  Research design was Completely Randomized Design (CRD) with treatments slurry dosages which were P0: without slurry, P1: 10/ha/year and P2: 20/ha/year. Parameters were chemical composition of slurry, microbial type and population, plant height, total leaf, stem diameter, number of branch and leaf size. The results showed that P0 had no significant effect on every parameters while P1 and P2 improved microbial type and population, plant height, total leaf, stem diameter, number of branch and leaf size (P <0.05). There was an increasing of microbial population in line with the increasing of slurry dosage. P2 contained the highest population of bacteria or fungal (P <0.05) compared to P0 while there was no sicnificant increased compare to P1. Keyword: Microbial, Biogas Slurry, Turi (Sesbania grandiflora)